Educating Through Attentional States of Consciousness, an Effective Way to Develop Creative Potential? - Rebecchi, Kevin; Hagège, Hélène (Frontiers in Education, 2022)
Researchers have recently turned their focus to a specific area: the links between altered states of consciousness and creativity. A spectrum of attentional states of consciousness exists, from hypnagogia and mind wandering to mindfulness and flow. These attentional states of consciousness are present during a variety of activities (e.g., sports, music, painting, writing, video games, theater, meditation) as well as in situations characterized by boredom. They are also present in many professional fields and practices (e.g., education and teaching). Moreover, researchers and educators focus sometimes on only one state of consciousness (such as mind wandering) or only on attention, and do not question relationships with others (such as mindfulness or flow) or the links with intention, the different levels of consciousness involved and the changes in perception of time, self and space. Additionally, as we know that a state of consciousness rarely occurs alone or that it can have two forms (such as spontaneous and deliberate mind wandering), we propose a global approach allowing to grasp the stakes and perspectives of what we call attentional states of consciousness. Thus, to our knowledge, this is the first theoretical review highlighting the historical, empirical, theorical and conceptual relationships between creativity, attention, mind wandering, mindfulness and flow by offering concrete and empirical avenues and bases for reflection about educating for creativity and developing creative potential.